Hubungan Dukungan Keluarga dengan Kepatuhan Diet Rendah Garam pada Pasien Hipertensi di GB3 Murni Teguh Memorial Hospital Medan - Valentino Pardede; Afnijar Wahyu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is a disease that is most commonly suffered by Indonesian people and can occur due to one of the problems that often arises from changes in lifestyle, such as consuming foods with high salt levels, obesity and stress. This study aims to determine the relationship between family support and adherence to a low salt diet in hypertensive patients at GB3 Murmur Memorial Hospital Medan. This research design uses descriptive correlation research with a cross sectional study approach. The data collection technique was carried out using total sampling with a total of 48 patients as respondents. The instrument used to collect data is a questionnaire. From the results of data processing using the Rank Spearman statistical test in SPSS For Windows 27 with a significance level of 95% (α = 0.05), a positive correlation value of 0.375 was obtained and a significant value of 0.009 (p<0.05). The conclusion of this study is that there is a significant relationship between family support and adherence to a low salt diet. For future researchers to make more samples and add independent variables such as knowledge, education, attitudes or motivation, the role of health worker.